Antibacterial and Wound Healing Activity In Vitro of Individual and Combined Extracts of Tagetes nelsonii Greenm, Agave americana and Aloe vera - Karen Alejandra Olán-Jiménez; Rosa Isela Cruz-Rodríguez; Beatriz del Carmen Couder-García; Nadia Jacobo-Herrera; Nancy Ruiz-Lau; Maritza del Carmen Hernández-Cruz; Víctor Manuel Ruíz-Valdiviezo (MDPI AG, 2024)
Currently, there are various physical and mechanical agents that can cause skin wounds, which are still traditionally treated with plant extracts. It has been reported that the genus Tagetes has a wide range of biological properties, including antibacterial and wound healing activity. Likewise, Agave americana extract and Aloe vera gel have shown potential in the treatment of burn wounds and other skin conditions both in vitro and in vivo. In this study, the antibacterial and wound healing activities of each of these plants were investigated, as well as the possibility of enhancing these activities by combining them. First, the secondary metabolites of the extracts were quantified, the antibacterial activity was evaluated using the Kirby-Bauer method, and their cytotoxicity was measured in 3T3 and HaCaT cells using the sulforhodamine B assay. The results revealed that Tagetes nelsonii extract had a higher amount of secondary metabolites, which is why it exhibited antibacterial activity. Finally, the scratch assay showed that the individual extracts of T. nelsonii and A. americana demonstrated greater cell migration and proliferation starting from 12 h, as well as when using the combination of A. americana extract and A. vera gel, which almost completely closed the wound compared to the control.